Do technology-based devices improve carious lesion detection? - Vitor, Luciana Lourenço Ribeiro; Kobayashi, Tatiana Yuriko; Carrara, Cleide Felicio Carvalho; Rios, Daniela; Silva, Thiago Cruvinel; Machado, Maria Aparecida Andrade Moreira; Oliveira, Thais Marchini (Brazilian Dental Science, 2016)
Objective: To compare the visual-tactile examination with the technology-based caries detection examinations in children. Methods: We assessed the teeth next to the cleft area of 95 children aged 6 to 12 years with oral clefts but without the presence of any associated syndrome or craniofacial anomaly, according to the following detection methods: visual-tactile examination (Method 1), visual-tactile examination through operating microscope (Method 2), visual examination through LED-based fluorescence device (Method 3), using ICDAS-II scores. The caries detection methods were compared by Friedman test (P<0.05). Results: The efficacy of carious lesion detection methods were statistically similar (P=0.786). Conclusions: Technology-based devices did not improve caries diagnosis in children because their results were similar to those of visual-tactile clinical examination. From a clinical point of view, we recommended the dentists to be cautious in using these additional diagnostic measures to avoid false positive errors mainly in tooth surfaces difficult to be examined. Keywords: Dental Caries. Lenses. Fluorescence. Cleft lip. Cleft palate.